The Impact of Physicians’ Reactions to Uncertainty on Patients’ Decision Satisfaction - Politi, Mary C. (2010)
RATIONALE: Patients’ and physicians’ response to uncertainty may affect decision outcomes. The purpose of this study was to explore the impact of patients’ and physicians’ reactions to uncertainty on patients’ satisfaction with breast health decisions. METHOD: Seventy-five women facing breast cancer prevention or treatment decisions and five surgeons were recruited from a Breast Health Center. Patients’ and physicians’ anxiety from uncertainty was assessed using the Physicians’ Reactions to Uncertainty Scale; wording was slightly modified for patients to ensure the scale was applicable. Patients’ decision satisfaction was assessed 1–2 weeks after their appointment. A mixed-effects logistic regression model was used to assess associations between patients’ and providers’ anxiety from uncertainty and patients’ decision satisfaction. A provider-specific random effects term was included in the model to account for correlation among patients treated by the same provider. RESULTS: Patients’ decision satisfaction was associated with physicians’ anxiety from uncertainty (beta = 0.92, p<0.01), but not with patients’ anxiety from uncertainty (beta = −0.18, p>0.27). CONCLUSIONS: This study suggests that physicians’ reactions to uncertainty may have an effect on decision satisfaction in patients. More research is needed to confirm this relationship and to determine how to help patient-provider dyads to manage the uncertainty that is inherent in most cancer decisions.